A "molecule pump" prototype for exceptionally high efficiency adsorption and decomposition of rhodamine B based on the TiO2@MIL-100 composite. Issue 3 (9th January 2017) - Chang, Na; Li, Yi-Xin; He, Dong-Ying; Tang, Zhi-Wei; Huang, Yan-Feng; Yu, Jing-Jian
Abstract : The fabricated TiO2 @MIL-100 composite not only demonstrates high capacity in adsorption of Rhodamine B (RhB) but also plays an important role as a "molecule pump" which offers excellent features and facilitates the following degradation of RhB with exceptionally high efficiency. Abstract : The fabricated TiO2 @MIL-100 composite not only demonstrates high capacity in adsorption of Rhodamine B (RhB) but also plays an important role as a "molecule pump" which offers excellent feature and facilitates the following degradation of RhB with exceptionally high efficiency.